Financial literacy: an exploratory review of the literature and future research - Mohamad Azmi Abdullah; Rosita Chong (UiTM Press, 2014)
There are voluminous literatures written on financial literacy or financial knowledge. Since there is a renewed interest in Islamic finance, this article provides an account of reviews on current financial literacy studies in particular studies with respect to Islamic financial products. It was several years ago when the Governor of Central Bank of Malaysia pointed out that in order to make Islamic financial products acceptable to a wider spectrum of investors and business people alike, financial literacy on Islamic financial products need to be enhanced. This is in order to facilitate transactions, with a clear understanding and appreciation of the unique characteristics and features of Islamic finance and its real economic value. Nevertheless, Kayed (2008) in his paper posed a pertinent question enquiring if there are any attempts by the research community to assess levels of Islamic financial literacy in various Muslim communities.In addition, another question was put forth by Ahmad (2010) on the importance of Islamic financial literacy. These two questions have actually motivated the current study to review available literatures on financial literacy main focus on the Islamic financial literacy. The objectives of this study are to determine if there are sufficient studies available on financial literacy with respect to Islamic financial products and services, as well as to examine if there are sufficient studies on the differences in the factors that affect financial literacy of people. The implications and recommendations are then put forward for future research.